2011
DOI: 10.3892/or.2011.1197
|View full text |Cite
|
Sign up to set email alerts
|

Growth of chronic myeloid leukemia cells is inhibited by infection with Ad-SH2-HA adenovirus that disrupts Grb2-Bcr-Abl complexes

Abstract: Abstract. the persistence of Bcr-Abl-positive cells in patients on imatinib therapy indicates that inhibition of the Bcr-Abl kinase activity alone might not be sufficient to eradicate the leukemia cells. Many downstream effectors of Bcr-Abl have been described, including activation of both the grb2-sos-ras-MApK and grb2-gab2-pI3K-Akt pathways. the Bcr-Abl-grb2 interaction, which is mediated by the direct interaction of the grb2 sH2 domain with the phospho-Bcr-Abl y177, is required for activation of these signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…At different time points (0 h, 24 h, 48 h, 72 h), cell proliferation assays using the MTT method were performed as described previously [10]. Cells were exposed to different concentrations of imatinib (Novartis) with different time (0 h, 24 h, 48 h, 72 h) and cell survival was measured by MTT assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At different time points (0 h, 24 h, 48 h, 72 h), cell proliferation assays using the MTT method were performed as described previously [10]. Cells were exposed to different concentrations of imatinib (Novartis) with different time (0 h, 24 h, 48 h, 72 h) and cell survival was measured by MTT assay.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysis, SDS-PAGE, and immunoblotting were done as described previously [10]. Antibodies against c-ABL, Bax, STAT5 and phosphorylated-STAT5, PARP, caspase 3 were from Cell Signaling Technology (Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…The SH2 domain of Grb2 had a high affinity with the phospho-Bcr-Abl Y177. In addition, we designed a mutant sequence (Sm) with one amino acid mutation (R27K) in the binding domain, which had been reported to block the binding to phospho-Bcr-Abl Y177 [23]. Each PCR fragment was cloned into the pAd5/F35-CMV plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction of Bcr-Abl Y177 with Grb2 potentially promotes association of Grb2-SH3 domains with guanine nucleotide exchange factor Sos, which can activate RAS by stimulating exchange of GDP for GTP [26]. Our previous works have demonstrated that the exogenous SH2 can disrupt the interaction between Grb2 and Bcr-Abl Y177, thus reducing MAPK and Akt kinase activities [23]. In this study, we constructed HF2S, which contains exogenous SH2 to specifically bind to the phospho-Y177 site of Bcr-Abl and transferred it into the nucleus by a combination of FN3R and AP21967.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation